An efficient aggregation‐enhanced delayed fluorescence luminogen created with spiro donors and carbonyl acceptor for applications as an emitter and sensitizer in high‐performance organic light‐emitting diodes. Issue 2 (2nd June 2022) - Chen, Hao; Zeng, Jiajie; Huang, Ruishan; Wang, Jianghui; He, Junchu; Liu, Hao; Yang, Dezhi; Ma, Dongge; Zhao, Zujin; Tang, Ben Zhong
Abstract: Organic light‐emitting diodes (OLEDs) fabricated using organic thermally activated delayed fluorescence materials as sensitizers have recently achieved significant advancements, but the serious efficiency roll‐offs are still troublesome in most cases. Herein, a tailor‐made multifunctional luminogen SBF‐BP‐SFAC containing 9, 9′‐spirobifluorene (SBF) and spiro[acridine‐9, 9‐fluorene] (SFAC) as electron donors and carbonyl as an electron acceptor is synthesized and characterized. SBF‐BP‐SFAC has the advantages of high thermal stability, aggregation‐enhanced delayed fluorescence, and balanced carrier transport ability, and prefers horizontal dipole orientation. Highly efficient OLEDs employing SBF‐BP‐SFAC as an emitter radiate intense cyan light with outstanding external quantum efficiencies ( η ext s) of up to 30.6%. SBF‐BP‐SFAC can also serve as an excellent sensitizer for orange fluorescence, phosphorescence, and delayed fluorescence materials, providing excellent η ext s of up to 30.3% with very small efficiency roll‐offs due to the fast Förster energy transfer as well as exciton annihilation suppression by bulky spiro donors. These outstanding performances demonstrate the great potential of SBF‐BP‐SFAC as an emitter and sensitizer for OLEDs. Abstract : An efficient aggregation‐enhanced delayed fluorescence luminogen (SBF‐BP‐SFAC) with high photoluminescence efficiency, balanced bipolar carrier transport, and horizontal dipole orientation is developed, which provides outstanding external quantum efficiencies of up to 30.6% as an emitter and 30.3% as a sensitizer for orange fluorescence, phosphorescence, and delayed fluorescence emitters with small efficiency roll‐offs.